For Our Children: A Research Study on Syrian Refugees’ Schooling Experiences in Ottawa - Nofal, Mozynah (Université d'Ottawa / University of Ottawa, 2017)
During 2015 – 2016, thousands of Syrian refugees arrived in Canadian cities, many of them hoping to find permanent settlement and new life opportunities. In the coming years, these refugees will form communities as they settle in Canada, and develop their own understandings of citizenship and belonging. Using an acculturation framework that views schooling as a primary shaper of resettlement experiences, this qualitative study draws on narrative methodology to explore the overarching question: What are the schooling experiences of recently arrived Syrian refugee within the Ottawa public school system? Refugee narratives describe hopes and concerns for the future, and provide insights for school administrators, educators, and policy makers into the previous experiences of refugees, and current challenges. Findings suggest Syrians arrive to Canada with a determination to succeed, and have positive initial schooling experiences, but often face challenges such as: lack of information, change in family roles, and language barriers.
Keywords: Refugee Education; Resettlement Studies; Acculturation; Refugee schooling